2020
DOI: 10.1142/s1793545820500297
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of potassium concentration with Vis–SWNIR spectroscopy in fresh lettuce

Abstract: Chronic kidney disease (CKD) is becoming a major public health problem worldwide, and excessive potassium intake is a health threat to patients with CKD. In this study, visible and short wave nearinfrared (Vis/SWNIR) spectroscopy and chemometric algorithms were investigated as a non-destructive method for assessing the potassium concentration in fresh lettuce to benefit chronic kidney disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The results show that the proposed methodologies can be used to predict CHL levels but not the other leaf metrics. In 2020, Xiong et al used Vis-SWNIR spectroscopy and chemometric techniques to investigate the potassium concentration in fresh lettuce [21]. The authors demonstrated how PLS and SVR can be used to assess potassium concentrations in these plants.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the proposed methodologies can be used to predict CHL levels but not the other leaf metrics. In 2020, Xiong et al used Vis-SWNIR spectroscopy and chemometric techniques to investigate the potassium concentration in fresh lettuce [21]. The authors demonstrated how PLS and SVR can be used to assess potassium concentrations in these plants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several classification methods were employed to classify agricultural products such as linear regression by partial least squares-discriminant analysis (PLS-DA) which was used to classify mandarin fruit from different canopy positions (Magsawa et al, 2012). Visible-short-wave nearinfrared (Vis-SWNIR) spectroscopy with partial least-squares (PLS) regression can detect and predict the potassium concentrations in fresh lettuce (Xiong et al, 2020). The NIR spectroscopy technique can be a good predictor of both chemical and physical parameters.…”
Section: Introductionmentioning
confidence: 99%